Penilaian Edukasi Bidan dan Kepatuhan Ibu Hamil melakukan Antenatal Care terhadap Pencegahan Preeklampsia - Sultina Sarita; Hasmia Naningsi; Nasrawati Nasrawati; Nirmawati Nirmawati (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2026)
Introduction and Method Preeclampsia is a pregnancy complication that can lead to maternal and fetal morbidity and mortality. This condition is characterized by an increase in blood pressure accompanied by proteinuria occurring after 20 weeks of gestation. This study was a quantitative observational study with a cross-sectional design. The population consisted of 107 third-trimester pregnant women in the working area of BLUD UPTD Puskesmas Perumnas, Kendari City. A sample of 52 respondents was selected. Data was collected using questionnaires and analyzed using the Chi-square test. Result Among the 52 respondents, midwife education assessment was predominantly in the "poor" category (23 respondents; 44.2%), maternal adherence to Antenatal Care (ANC) was mostly "non-adherent" (29 respondents; 55.8%), and preeclampsia prevention efforts were largely in the "not performing" category (30 respondents; 57.7%). Data analysis revealed a significant relationship between midwife education assessment and preeclampsia prevention efforts (Χ2 = 8.649 > Χ2 table = 5.99 p = 0.013 ≤ 0.05). Furthermore, a significant relationship was found between maternal adherence to ANC and preeclampsia prevention efforts (Χ2 = 5.882 > Χ2 table = 3.841 p = 0.016 ≤ 0.05). Conclusion and Recommendation There is a significant relationship between midwife education assessment and maternal adherence to ANC with preeclampsia prevention efforts in the working area of BLUD UPTD Puskesmas Perumnas, Kendari City. Midwives are encouraged to enhance their health education delivery by utilizing accessible and simplified language, particularly regarding preeclampsia prevention. Furthermore, future studies should incorporate additional variables—such as family support, educational attainment, and access to digital health platforms (e.g., pregnancy-related mobile applications)—which may significantly influence adherence levels and the overall effectiveness of preeclampsia prevention efforts.  Contribution to the Sustainable Development Goals (SDGs) This research directly contributes to SDG 3 (good health and well-being), specifically target 3.1, which aims to reduce the maternal mortality ratio. These findings support national health priorities by strengthening the role of primary healthcare (Puskesmas) in early preeclampsia detection and management by optimizing midwife-led education and maternal adherence to antenatal care.